Die Globalisierung — eine umkehrbare Geschichte? - Werner Plumpe (Wirtschaftsdienst, 2017)
Globale Arbeitsteilung mit globalem Handelsaustausch hat es schon immer gegeben. Mittlerweile machen geringe Transportkosten diese Arbeitsteilung intensiver - auch bedingt durch den beispiellosen Abbau von Handelshemmnissen nach dem Zweiten Weltkrieg. Die Wohlfahrtseffekte des internationalen Handels waren und sind allerdings ungleich verteilt, was immer wieder zu Konfl ikten führt. Aus der Geschichte ist vor allem die Lehre zu ziehen, dass es keine Vorteile bringt, die internationale Arbeitsteilung zu begrenzen. Wenn dies aber doch als nötig angesehen wird, sollte der mögliche Zeitgewinn bei der Anpassung an den internationalen Wettbewerb für Strukturreformen genutzt werden. Ein dauerhafter Ausstieg aus der internationalen Arbeitsteilung hat sich nie als erfolgreich erwiesen. – – A global labour division with a corresponding exchange in trade has always existed, ultimately for reasons of pragmatism; the volume and structure of this labour division did particularly depend on technical and economic conditions. Today, low haulage makes the division of labour exceedingly intense, supported by the unprecedented reduction of trade barriers in the Post-War period. The latter phenomenon had always been controversial, as impacts of global trade on welfare were, and still are, unequally distributed. The winners seek to secure their advantages, while the losers try to defend themselves against competitors. There are two lessons to be learned from historic experience: On the one hand, that a limitation of global labour division is altogether unfavourable; first, that the costs resulting from an occasional limitation are only acceptable under the premise that the time gained is used for structural reforms that allow the return to the global division of labour. A permanent exit from global economy, however, has (thus far) never turned out to be successful.
Keywords: F10; F60; N70; 330